Natural Products for the Management of Castration-Resistant Prostate Cancer: Special Focus on Nanoparticles Based Studies - Singla, Rajeev K.; Sai, Chandragiri Siva; Chopra, Hitesh; Behzad, Sahar; Bansal, Himangini; Goyal, Rajat; Gautam, Rupesh K.; Tsagkaris, Christos; Joon, Shikha; Singla, Shailja; Shen, Bairong (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer is the most common type of cancer among men and the second most frequent cause of cancer-related mortality around the world. The progression of advanced prostate cancer to castration-resistant prostate cancer (CRPC) plays a major role in disease-associated morbidity and mortality, posing a significant therapeutic challenge. Resistance has been associated with the activation of androgen receptors via several mechanisms, including alternative dehydroepiandrosterone biosynthetic pathways, other androgen receptor activator molecules, oncogenes, and carcinogenic signaling pathways. Tumor microenvironment plays a critical role not only in the cancer progression but also in the drug resistance. Numerous natural products have shown major potential against particular or multiple resistance pathways as shown by in vitro and in vivo studies. However, their efficacy in clinical trials has been undermined by their unfavorable pharmacological properties (hydrophobic molecules, instability, low pharmacokinetic profile, poor water solubility, and high excretion rate). Nanoparticle formulations can provide a way out of the stalemate, employing targeted drug delivery, improved pharmacokinetic drug profile, and transportation of diagnostic and therapeutic agents via otherwise impermeable biological barriers. This review compiles the available evidence regarding the use of natural products for the management of CRPC with a focus on nanoparticle formulations. PubMed and Google Scholar search engines were used for preclinical studies, while ClinicalTrials.gov and PubMed were searched for clinical studies. The results of our study suggest the efficacy of natural compounds such as curcumin, resveratrol, apigenin, quercetin, fisetin, luteolin, kaempferol, genistein, berberine, ursolic acid, eugenol, gingerol, and ellagic acid against several mechanisms leading to castration resistance in preclinical studies, but fail to set the disease under control in clinical studies. Nanoparticle formulations of curcumin and quercetin seem to increase their potential in clinical settings. Using nanoparticles based on betulinic acid, capsaicin, sintokamide A, niphatenones A and B, as well as atraric acid seems promising but needs to be verified with preclinical and clinical studies.